2006
DOI: 10.1007/s11262-005-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of a new mammalian reovirus, type 2 Winnipeg (T2W)

Abstract: We previously described isolation of a potentially new reovirus strain from the central nervous system of an 8-week-old female infant with a history of active varicella, oral thrush, hypoalbuminemia, intermittent fevers, diarrhea and feeding intolerance [Hermann et al., Ped. Inf. Dis J. 23, 373 (2004)]. This reovirus strain was tentatively identified as a member of the serotype 2 group by virus neutralization and RNA-gel electrophoresis studies and has been named type 2 Winnipeg (T2W). For this study we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…In humans, MRVs are mainly responsible for respiratory and/or enteric disease. However, previous studies have reported the isolation of the three different serotypes of MRV on cell culture from cerebrospinal fluid of patients with meningitis (Johansson et al., 1996; Hermann et al., 2004; Tyler et al., 2004; Jiang et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, MRVs are mainly responsible for respiratory and/or enteric disease. However, previous studies have reported the isolation of the three different serotypes of MRV on cell culture from cerebrospinal fluid of patients with meningitis (Johansson et al., 1996; Hermann et al., 2004; Tyler et al., 2004; Jiang et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although reovirus infection of humans usually induces mild symptoms, infection of newborn mice leads to severe pathologic conditions, such as lethal encephalitis, depending on the inoculation route and strain (4,5). Previous studies have described the isolation of 3 reovirus strains after cell culture of cerebrospinal fl uid (CSF) from patients with meningitis: serotype 1 (6), serotype 3 (T3C96) (7), and serotype 2 (T2W) (8,9). The etiologic role of the T2W strain in meningitis could not be ascertained because the patient was co-infected with other agents (8).…”
Section: Ammalian Reoviruses Members Of the Genusmentioning
confidence: 99%
“…In order to perform genomic sequencing, complementary DNA (cDNA) was generated following the method outlined by Jiang et al [30]. Primers were designed to amplify specific viral genes, and the PCR products were sequenced at the University of Guelph Laboratory Services, Guelph, ON, Canada.…”
Section: Methodsmentioning
confidence: 99%